Scientific and methodical work in higher pedagogical educational establishment as a system - Степанець, І. О. (Scientific notes of the pedagogical department, 2019)
The problem of systemacity of scientific and methodical work as an interactive complex dynamical structurized linking of scientific and researching and methodical work is raised in the article.The scientific and pedagogical work of higher pedagogical educational establishment as a component of the general pedagogical system, which together with its other components formed scientific and theoretical (conceptual) and processual unity is characterised.It is specified contradictions determining the needs and indicating the directions of forming integral system of scientific and methodical work, particularly in higher pedagogical educational establishments.Based on the results of analysis of scientific works, specific methodological and organizational and substantive aspects of formation and development of scientific and methodical work in higher pedagogical educational establishments are highlighted.On the basis scientific generalizations and experience of pedagogical activity a system of scientific and methodical work in higher pedagogical educational establishments, creating potential connections and interconnections of its objects and subjects.The most substantial system features of scientific and methodical work in higher pedagogical educational establishments on the basis of systematic approach to study of objects and phenomenon of pedagogical activityare distinguished and characterized.